Konsep Keadilan Sosial Dalam Al-Qur’an Perspektif Tafsir Maudhu’i Terhadap Ayat-Ayat Al-‘Adl - Zul Zami (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research examines the concept of social justice in the Qur'an as a main pillar in building a harmonious, balanced, and civilized life. The method used is library research with a maudhu'i (thematic) interpretation approach. This study collects and analyzes verses related to al-'adl along with its derivations and equivalents to obtain a comprehensive and contextual understanding. The results show that justice in the Qur'an is not only normative as a moral value but also operational, which must be realized in various dimensions of life, including legal, social, economic, political, and moral aspects. Justice is defined as placing something proportionally, granting rights to those who are entitled, and maintaining balance without discrimination, thus reflecting substantive justice, not mere formality. In the contemporary context, this concept is relevant as a solution to various problems such as economic inequality, discrimination, and moral crisis. Thus, social justice in the Qur'an is an integral and transformational value system that acts as a driving force for change toward a just, peaceful, and sustainable society